Laboratory-Based Surveillance of Tuberculosis Disease in BTKLPP Ambon - Zusana Lena Tulak; Budi Santoso; Richard D. Nahumury; Sahriyana (Universitas Mandala Waluya, 2023)
Tuberculosis is still a health problem that is a global burden. Indonesia is the third-ranked country in the world with the highest TB burden, and in Ambon City, there are 1296 TB sufferers. The purpose of this laboratory-based surveillance is to describe the situation of TB disease in the Ambon Class II BTKLPP service area during 2022. This activity is operational research that monitors and evaluates the results of an examination of TB specimens sent by health facilities or those taken by themselves by Ambon Class II BTKLPP officers in TB screening activities in special places. Materials and tools used in examining TB specimens include sputum, TCM GeneXpert-TB, and other supporting materials. The results of the TB specimen examination are recorded in the TB Information System (SITB), which is a TB surveillance tool used to monitor TB cases in Indonesia. The results of this activity included: of the 347 TB samples examined, 15% were drug-sensitive TB, 1% were rifampicin-resistant TB, 2% were error, and 82% were negative. The conclusion there are still drug-sensitive TB and resistant TB in the Ambon BTKLPP service area. This activity needs to be continued so that TB cases in service areas can be monitored.